The Best Approximation by Using Bernstein's Polynomial in Lp [0,1] - Mezaal, Ahmed Abbas (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
We estimate in this paper the degree of approximation of [0,1]by using Bernstein's polynomial involving on Ditizian-Totik modulus of smoothness . On the other hand, we consider this polynomial to obtain an equivalence approximation theorem with this modulus.